The Islamic Approaches For Emotional Symptoms Of Premenstrual Syndrome (PMS) - Nurul Hanis Sufia Othman; Faisal Ahmad Shah; Ishak Hj Suliaman; Sharifah Basirah Syed Muhsin (Universiti Sains Islam Malaysia, 2024)
Journal of Islamic Social Sciences and Humanities volume 30 Issue 1 Page (1-24)